Covenantal and dispensational theologies : four views on the continuity of Scripture - Parker, Brent E., 1978-; Lucas, Richard James, 1981- (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2022)
"How do the Old and New Testaments relate to each other? What is the relationship among the biblical covenants? In this volume in IVP Academic's Spectrum series, readers will find four contributors who explore these complex questions, each making a case for their own view and responding to the others' views to offer an animated yet irenic discussion on the continuity of Scripture"--
Introduction to covenantal and dispensational theologies: four views on the continuity of Scripture / Brent E. Parker and Richard J. Lucas -- Main Essays -- Covenant Theology / Michael S. Horton -- Progressive Covenantalism / Stephen J. Wellum -- Progressive Dispensationalism / Darrell L. Bock -- Traditional Dispensationalism / Mark A. Snoeberger -- Responses -- A Covenant Theology Response / Michael S. Horton -- A Progressive Covenantalism Response / Stephen J. Wellum -- A Progressive Dispensationalism Response / Darrell L. Bock -- A Traditional Dispensationalism Response / Mark A. Snoeberger -- Conclusion / Brent E. Parker and Richard J. Lucas.
Includes bibliographical references and indexes.
Keywords: Bible -- Criticism, interpretation, etc; Covenant theology; Dispensationalism; Criticism, interpretation, etc